PENINGKATAN PROSES PEMBELAJARAN DENGAN MENGGUNAKAN MEDIA ELEKTRONIK - Siti Nur Barokah; Hadiahti Utami; Taviyastuti Taviyastuti; Fatchun Hasyim (Admisi dan Bisnis, 2017)
Early Childhood Education (PAUD), is a coaching effort aimed at children from birth up to theage of 6 years is done through the provision of educational stimuli to help growth and physicaland spiritual development so that children have readiness in entering further education. TKAisyiyah Bustanul Athfal 48 Pedurungan-Semarang is an Islamic Early Childhood educationalinstitution with emphasis on faith, worship and morals through religious understanding such as:recitation of prayers, prayer readings, prayer practice, writing and reading qiroaty and others .Learning process is done in kindergarten Aisyiyah Bustanul Athfal still use manual ways.Therefore it is necessary to develop the learning process by using the LCD Projector technologywhich is equipped with thematic VCD using the appropriate learning model. The purpose of theimplementation of Community Service activities in kindergarten ABA 48 is to open the teacher'sinsight to further improve the quality of learning process by using LCD Projector propsequipped with thematic VCD with certain learning model. Implementation of Community Serviceactivities using training methods, mentoring and simulation. With the training, mentoring andsimulation to partners in this case the kindergarten teachers ABA 48 expected to providesolutions that suit the needs.